Mindfulness-Integrated Management to Elevate Student Resilience in Modern Islamic Boarding Schools - Harun Lubis; Agus Salim Salabi (Program Studi Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2025)
This study aims to analyze the integration of mindfulness into the management of Islamic education in modern Islamic boarding schools, identify key factors affecting students' resilience, and evaluate the effectiveness of mindfulness practices in enhancing students' mental and emotional resilience in facing challenges. Method: This research employs a qualitative library research method with a descriptive-analytical approach. Data were systematically collected from reputable journal articles, research reports, books, and relevant documents indexed in databases such as Google Scholar, JSTOR, and ScienceDirect. Content analysis was applied to identify themes, patterns, and conceptual relationships related to mindfulness integration, Islamic educational management, and student resilience. Data validity was ensured through triangulation and cross-referencing with established theories. The findings indicate that mindfulness integration in modern Islamic boarding schools focuses on holistic development through practices such as meditation, self-reflection, and breathing exercises. Key challenges undermining student resilience include academic pressure, difficulties with socio-cultural adaptation, and identity conflicts. Mindfulness practices have been shown to enhance resilience by improving stress management, self-awareness, emotional regulation, and adaptive coping strategies. The integration of mindfulness into Islamic education management significantly contributes to the development of student resilience. This approach not only aligns with Islamic spiritual values but also fosters a supportive educational environment that promotes mental and emotional well-being. The study recommends implementing structured mindfulness training for educators and students, integrating mindfulness practices into the curriculum, and developing institutional support systems. These steps are essential for creating resilient educational communities capable of navigating modern challenges while preserving Islamic educational values. Further cross-institutional collaboration and empirical research are encouraged to broaden the applicability of the findings.